(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Objective: To test the use of Moyers prediction method and Tanaka and Johnstons equations for use in a Bangladeshi population and to construct new probability tables and prediction formulae based on the actual tooth sizes in a sample of the Bangladeshi population. Design of the study: Descriptive cross-sectional study. Materials and Methods: The sample was consisted of 50 Bangladeshi males and 50 females aged between 17 and 23 years. Subjects without any previous orthodontic treatment fully erupted permanent teeth and with no dental anomalies were recruited. Dental study models were taken and measurements of the mesio-distal widths of teeth were carried out using digital caliper. The measured values were compared with predicted values derived from Moyers method and Tanaka and Johnston equations. Independent t tests were used to examine differences between genders. Correlation coefficients and linear regression equations were used to compare the actual Bangladeshi tooth widths with predicted values. Results: For Bangladeshi males, Moyers method at 50% tends to overestimate the actual value of the canines and premolars by 0.3 mm with a standard deviation of 0.08 mm, whereas the Tanaka and Johnston method tends to overestimate the actual value of the canines and premolars by 1.4 mm with a standard deviation of 0.11 mm. For Bangladeshi females, Moyers method at 50% tends to overestimate the actual value of the canines and For Bangladeshi females, Moyers method at 50% tends to overestimate the actual value of the canines and to overestimate the actual value of the canines and premolars by 1.4 mm with a standard deviation of 0.13 mm. Conclusion: The newly developed regression equations are more accurate for prediction of width of unerupted permanent teeth in a Bangladeshi population. Further studies are required based on larger sample size, to confirm the applicability of the new regression equations proposed. Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1